A Zero-Equation Model for External Aerodynamics (MIST International Journal of Science and Technology, 2023)
The zero-equation model (ZEM) has been generalized for aerodynamic applications by eliminating the thickness of boundary-layer (BL) dependency to construct the stress length parameter . The SED (Structural Ensemble Dynamics) postulate evaluates the using the order function based on universal multi-layer structures for wall turbulence. The SED concept is further employed to optimize the profiles of the turbulent kinetic energy and dissipation rate with turbulent BL flows. Results demonstrate that the multilayer ZEM receives a remarkable achievement in the prediction of wall-bounded turbulence and thus, prevails over the drawbacks encountered in most algebraic turbulence models.MIJST, Vol. 11, June 2023 : 21-30DOI: https://doi.org/10.47981/j.mijst.11(01)2023.403(21-30)